2014
DOI: 10.1038/ncb3040
|View full text |Cite
|
Sign up to set email alerts
|

ΔNp63 promotes stem cell activity in mammary gland development and basal-like breast cancer by enhancing Fzd7 expression and Wnt signalling

Abstract: Emerging evidence suggests that cancer is populated and maintained by tumor initiating cells (TICs) with stem-like properties similar to that of adult tissue stem cells. Despite recent advances, the molecular regulatory mechanisms that may be shared between normal and malignant stem cells remain poorly understood. Here we show that the ΔNp63 isoform of the Trp63 transcription factor promotes normal mammary stem cell (MaSC) activity by increasing the expression of the Wnt receptor Fzd7, thereby enhancing Wnt si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
216
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 190 publications
(245 citation statements)
references
References 66 publications
28
216
1
Order By: Relevance
“…cbioportal.org/). As previously reported (11), our analysis of the METABRIC dataset confirmed that expression of p63 is also significantly correlated with expression of Fzd7 in patients with breast cancer, at least when using one of two distinct probes (Fig. S5 B-D).…”
Section: Depletion Of P63 In Erbb2 Progenitors Attenuates Mammary Tumorsupporting
confidence: 68%
See 3 more Smart Citations
“…cbioportal.org/). As previously reported (11), our analysis of the METABRIC dataset confirmed that expression of p63 is also significantly correlated with expression of Fzd7 in patients with breast cancer, at least when using one of two distinct probes (Fig. S5 B-D).…”
Section: Depletion Of P63 In Erbb2 Progenitors Attenuates Mammary Tumorsupporting
confidence: 68%
“…For instance, p63 regulates the expression of several molecules of the Notch pathway (28,29). Moreover, in basal-like breast tumors, ΔNp63 regulates CSC properties through the induction of Fzd7 expression and subsequent activation of the Wnt/β-catenin pathway (11). To assess whether p63 also promotes SC activity through the modulation of these two pathways, we measured the expression levels of Notch receptors and Notch target genes, as well as the expression levels of Fzd7, in p63-depleted ErbB2 mammospheres.…”
Section: Depletion Of P63 In Erbb2 Progenitors Attenuates Mammary Tumormentioning
confidence: 99%
See 2 more Smart Citations
“…Along these lines, p63 normally antagonizes oncogenic TGF-β signaling and its stimulation of tumor development and metastatic progression. However, mutant p53 can form a ternary complex with TGF-β-regulated Smads and p63, thereby inactivating the tumor suppressing activities of p63 and enabling the tumor promoting properties of TGF-β, including its stimulation of metastasis and CSC self-renewal (20,21).…”
Section: Epigenetic Modulation Of Emt: Chromatin States Prime Cscs Fomentioning
confidence: 99%